Non-invasive Assessment of Mitochondrial Oxygen Metabolism in the Critically Ill Patient Using the Protoporphyrin IX-Triplet State Lifetime Technique—A Feasibility Study - Neu, Charles; Baumbach, Philipp; Plooij, Alina K.; Skitek, Kornel; Götze, Juliane; von Loeffelholz, Christian; Schmidt-Winter, Christiane; Coldewey, Sina M. (Frontiers in Immunology, 2020)
The imbalance of oxygen delivery and oxygen consumption resulting in insufficient tissue oxygenation is pathognomonic for all forms of shock. Mitochondrial function plays an important role in the cellular oxygen metabolism and has been shown to impact a variety of diseases in the intensive care setting, specifically sepsis. Clinical assessment of tissue oxygenation and mitochondrial function remains elusive. The in vivo protoporphyrin IX‐triplet state lifetime technique (PpIX-TSLT) allows the direct, non-invasive measurement of mitochondrial oxygen tension (mitoPO2) in the human skin. Our recently established measurement protocol for the Cellular Oxygen Metabolism (COMET) Monitor, a novel device employing the PpIX-TSLT, additionally allows the evaluation of oxygen consumption (mitoVO2) and delivery (mitoDO2). In the intensive care setting, these variables might provide new insight into mitochondrial oxygen metabolism and especially mitoDO2 might be a surrogate parameter of microcirculatory function. However, the feasibility of the PpIX-TSLT in critically ill patients has not been analyzed systematically. In this interim study analysis, we evaluated PpIX-TSLT measurements of 40 patients during the acute phase of sepsis. We assessed a) potential adverse side effects of the method, b) the rate of analyzable measurements, c) the stability of mitoPO2, mitoVO2 and mitoDO2, and, d) potential covariates. Due to excessive edema in patients with sepsis, we specifically analyzed the association of patients’ hydration status, assessed by bioimpedance analysis (BIA), with the aforementioned variables. We observed no side effects and acquired analyzable measurements sessions in 92.5% of patients (n=37/40). Different measures of stability indicated moderate to good repeatability of the PpIX-TSLT -variables within one session of multiple measurements. The determined limits of agreement and minimum detectable differences may be helpful in identifying outlier measurements. In conjunction with signal quality they mark a first step in developing a previously unavailable standardized measurement quality protocol. Notably, higher levels of hydration were associated with lower mitochondrial oxygen tension. We conclude that COMET measurements are viable in patients with sepsis. To validate the clinical and diagnostic relevance of the PpIX-TSLT using the COMET in the intensive care setting, future studies in critically ill patients and healthy controls are needed.